The romance of Ali Mahmoud Taha Al-Muhandis and its impact on the poetry of Nazik Al-Malaika (Journal of the College of Basic Education, 2022)
It is wrong to believe that the existence of a relationship (influence and influence) between one poet and another reduces the originality or quality of the literary work compared to its previous counterpart. Literary works to conduct and influence the reader, and that every poet puts himself under the influence of another poet with whom he is associated with a relationship that is: a mixture of affection and discussion, similar to the relationship between children and parents in the Freudian concept, and that every new literary work is linked to the previous works, affected by it and influenced by it. In which ; This means: that the impact is inevitably expected, and that it constitutes a basis for creativity and innovation, which is what we are trying to clarify through our study of the romance of Ali Mahmoud Taha Al-Muhandis and its impact on the poetry of Nazik Al-Malaika.